73.9k views
5 votes
-2x + y =0
5x + 3y = -11

User Shark
by
5.7k points

1 Answer

3 votes

Answer:

(-1, -2)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination
  • Solving systems of equations by graphing

Explanation:

Step 1: Define Systems

-2x + y = 0

5x + 3y = -11

Step 2: Rewrite Systems

-2x + y = 0

  1. Add 2x on both sides: y = 2x

Step 3: Redefine Systems

y = 2x

5x + 3y = -11

Step 4: Solve for x

Substitution

  1. Substitute in y: 5x + 3(2x) = -11
  2. Multiply: 5x + 6x = -11
  3. Combine like terms: 11x = -11
  4. Isolate x: x = -1

Step 5: Solve for y

  1. Define equation: y = 2x
  2. Substitute in x: y = 2(-1)
  3. Multiply: y = -2

Step 6: Graph Systems

Check the solution set.

-2x + y =0 5x + 3y = -11-example-1
User Helen Hakobyan
by
5.4k points